Warm-cold rolling enhances the heterogeneity of austenitic stainless steel: Achieving a match of high strength and ductility - Shuyi Quan; Shengrui Su; Renbo Song; Changhong Cai; Kaikun Wang (Journal of Materials Research and Technology)
A heterostructure austenitic stainless steel was prepared using a novel strategy of warm rolling, cold rolling and short-time annealing (WCA). The tensile strength of 1239 MPa, yield strength of 1122 MPa, and total elongation of 29.4 % was obtained. Compared with the traditional two-step cold rolling annealing process (CACA), the WCA process can enhance structural heterogeneity, substantially increasing ductility at a comparable yield strength. This is mainly due to the inhibition of strain-induced martensite transformation, the retention of large deformed austenite grains, and the pinning effect of nano Cu-rich precipitates on grain boundaries. Hetero-deformation induced strengthening and precipitation strengthening compensate for the dislocation strengthening and grain boundary strengthening. A higher proportion of large-sized fine grains and smaller Cr-rich precipitates contribute to the sustained strain hardening. This work provides a new strategy for preparing austenitic stainless steel with excellent mechanical properties and has important industrial application potential.